KAJIAN PEMODELAN ARUS DAN SEDIMEN DI SEKITAR JETTY MUARA SUNGAI - Priyo Nugroho Parmantoro (Diponegoro University, 2013)
The use of models in the design of jetties at the river mouth is intended to achieve efficiency and predict the function of events forces the river and marine hydrodynamics in a variety of scenarios handling of sedimentation in the estuary. One of the aspects of impacts of current changes that are modeled around the estuary in both the condition before treatment and after a jetty. While other aspects that need to be considered is the hydraulics of the river in the upper-estuary, shoreline change and ocean wave characteristics around the mouth of the river jetty. To be able to know the current pattern of movement around the mouth of the river jetty used models of Surface Water Modeling System (SMS) As a research object is used Silandak Jetty. It has the data before the jetty was built so that could be compared with the condition in which the jetty has been built. Current survey results that occurred in these waters is caused by tidal forces and non tidal. Due to the influence of tides, currents tend to back and forth in a certain direction (from the sea into the estuary). While the non-tidal forces tend to be dominated by the longshore current (caused by the influence of the wave). The simulation result shows a flow that at low tide the sea water circulation in the waters in Silandak moving toward the west to the northwest while the tide moves in the opposite direction heading east with a range between 0,05 to 0,25 m/sec. Sediment modelling shows that flushing sediment has effectively result. Key words: Jetty, Current, Sediment